EFECT OF INCOME SMOOTHING ON PRICE EARNING RATIO - arliansyah arliansyah (Universitas Negeri Medan (UNIMED), 2018)
This study allegedly reporting accounting earnings prepared by managers, attempting to level income year after year for variability of reporting can be suppressed and stock prices can be affected.This study was conducted to determine the effect of income smoothing index on Price Earning Ratio (PER), where the research design is conducted to answer whether the issuer of financial and non finance doing income smoothing action. Tests conducted on 70 companies listed on the Indonesia Stock Exchange.Data were tested by statistical tests in general and test for each hypothesis. The results of the study found that all hypothesized factors had no effect on income smoothing.